Coxiella burnetii serostatus in dromedary camels (Camelus dromedarius) is associated with the presence of C. burnetii DNA in attached ticks in Laikipia County, Kenya - Rooney, T.; Fèvre, Eric M.; Villinger, J.; Brenn-White, M.; Cummings, C.O.; Chai, D.; Kamau, J.; Kiyong’a, Alice; Getange, D.; Ochieng, D.O.; Kivali, Velma; Zimmerman, D.; et al. (Wiley, 2024)
Aims